A six-weekly dosing schedule for pembrolizumab in patients with cancer based on evaluation using modelling and simulation. (May 2020) - Lala, Mallika; Li, Tommy Ruosi; de Alwis, Dinesh P.; Sinha, Vikram; Mayawala, Kapil; Yamamoto, Noboru; Siu, Lillian L.; Chartash, Elliot; Aboshady, Hesham; Jain, Lokesh
Abstract: Background: Pembrolizumab is approved for multiple cancer types at 200 mg and 2 mg/kg dose every 3 weeks (Q3W). We used a model-based approach to compare the exposure of pembrolizumab 400 mg dose every 6 weeks (Q6W) with the Q3W regimens. Methods: The Q6W dose was selected by matching exposure with the 200 mg and 2 mg/kg Q3W doses. Concentration-time profiles were simulated using the established population pharmacokinetic model of pembrolizumab based on 2993 subjects from five clinical trials across tumour types. Efficacy was bridged by evaluating projections of average concentration over the dosing interval (Cavg ) and trough concentration (Cmin ) at steady state (ss ). Safety was bridged by ensuring that concentrations were below those at 10 mg/kg dose every 2 weeks (Q2W), the maximum clinical dose. Results: The 400 mg Q6W dose had similar predicted exposure (Cavg, ss, geometric mean ∼1% higher) as the 200 mg Q3W dose. Fewer than 1% of subjects had transiently lower Cmin, ss than that observed for 200 mg and 2 mg/kg Q3W. Despite these reductions, similar target saturation is expected. The predicted peak concentrations (Cmax, ss ) for 400 mg Q6W were substantially (∼65%) lower than the 10 mg/kg Q2W dose. Conclusions: Exposures expected for pembrolizumab 400 mg Q6W were similar to the 200 mg and 2 mg/kg Q3W and below the 10 mg/kg Q2W regimens. Established exposure-response relationships for pembrolizumab over a 5-fold dose range (2 mg/kg Q3W to 10 mg Q2W) support that clinical efficacy and safety of 400 mg Q6W would be similar to the 200 mg and 2 mg/kg Q3W doses across tumour types. Clinical trial registration numbers: NCT01295827, NCT01704287, NCT01866319, NCT01905657, NCT02142738. Highlights: Extended dosing of pembrolizumab will provide greater convenience and flexibility. Exposure of pembrolizumab 400 mg Q6W and Q3W regimens was compared using modelling. Pembrolizumab 400 mg Q6W leads to similar exposures as 200 mg and 2 mg/kg Q3W. Similar efficacy and safety of the pembrolizumab Q6W and Q3W regimens is expected.